Argument z wyobrażalności a strategia pojęć fenomenalnych - Polcyn, Karol (Filozofia Nauki, 2005)
According to the conceivability argument, physicalism is false since it is conceivable and hence possible that the physical truth do not entail the phenomenal truth. The influential way of responding to the conceivability argument is to claim that our conceivability intuitions can be accounted for in purely psychological terms, by appealing to some cognitive and functional differences between phenomenal and physical concepts, and that therefore what is conceivable does not entail what is possible. On this account, the entailment from the physical to the phenomenal that physicalism is committed to can be necessary and a posteriori. I argue that this way of responding to the conceivability argument cannot work. The conceivability argument depends on an assumption which implies that the psychophysical entailment cannot be necessary and a posteriori and appealing to the differences between phenomenal and physical concepts has no force against that assumption.